(untitled) (Mustansiria Dental Journal, 2018)
The aim of the this study was to investigate the efficacy of ProTaper rotary instruments compared to hand instrumentation with Hedstrom files, with and without the use of a solvent (eucalyptol) in the retreatment of gutta-percha filled root canals. Roots of forty extracted single-rooted maxillary anterior teeth with straight root canals were utilized in this study. The root canals were prepared using step-back technique and obturated with laterally condensed gutta-percha and sealer cement. The roots randomly divided into four groups with ten specimens each. Removal of gutta-percha was performed using ProTaper and Hedstrom files, both were used with and without the solvent eucalyptol. Both, time taken to reach the working length and time taken to complete removal of gutta-percha were recorded. Statistical analysis of the collected data revealed a highly significant decrease in the working time when ProTaper was used to remove gutta-percha compared with Hedstrom files. A highly significant decrease in the working time was found when eucalyptol was used with ProTaper. No significant difference existed between the treatments using Hedstrom with or without the use of eucalyptol.